Optical-helicity-driven magnetization dynamics in metallic ferromagnets - Gyung-Min Choi (Nature Portfolio, 2017)
Optical switching of ferromagnets has attracted interest for use in ultrafast spintronics but the physical origin of the effect remains unclear. Here the authors determine the contributions of two proposed mechanisms, the inverse Faraday effect and optical spin-transfer torque.